New deformation-controlled design of reinforced concrete flexural members subjected to blast loadings - Li, Bing (2014)
Both maximum displacement and displacement ductility factor should be considered in the design of a blast resistant structure since both the parameters correlate with an expected performance level of a reinforced concrete (RC) structural member during a blast event. Assuming that the actual responses of a RC member are equal to those of the equivalent SDOF system, an iterative design procedure is developed for RC structural members on the basis of non-dimensional energy spectra (NES), which are constructed from an elastic-perfectly-plastic single-degree-of-freedom (SDOF) system. By converting a RC member into an equivalent SDOF system and controlling the responses of maximum displacement and displacement ductility factor to exactly reach the corresponding design performance targets, the effective depth and the longitudinal reinforcement ratio of the RC member are specifically determined against the given blast loading within the design process. To evaluate the design validity, numerical analysis is carried out on the specifically designed member to compute its actual responses under the given blast loading and compare these with the design performance targets. Some differences have been observed due to simplifying assumption of converting the RC member into an equivalent SDOF system.